RAPID PROTOTYPING TECHNOLOGY - Md. Saidin Wahab (2017)
The purpose of this book is to provide an introduction to the fundamental principles and application area in Rapid Prototyping (RP) technology. The book traces the development of RP in the arena of Advanced Manufacturing Technologies and explains the principles underlying each of the RP technologies. It also covered the most dominant RP processes and their specifications, in particular of selective laser sintering (SLS) process. The material in this book has been used and revised several times for professional courses conducted for academia since 2008. Certain materials were borne out of research conducted in the School of Mechanical Engineering at the University of Leeds. To be used more effectively for graduate or final year undergraduate student in Manufacturing Engineering.